2013
DOI: 10.1097/prs.0b013e31829acc60
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Use in Cosmetic Plastic Surgery

Abstract: Steroid use is not warranted in the postoperative period and only reduces transient edema and ecchymosis. A significant benefit for steroid use after rhytidectomy is not evident as well. Steroid use may benefit in postoperative nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 28 publications
1
40
1
2
Order By: Relevance
“…Administering a single perioperative dose of dexamethasone decreases edema and ecchymosis formation over the first 2 postoperative days 97 ; there is also evidence that corticosteroids decrease pain and discomfort. 15,98,99 In addition, corticosteroids reduce nausea and vomiting in the immediate postoperative period, which may improve patient satisfaction. Conversely, there is some evidence that perioperative steroids may prolong postoperative ecchymosis 100 (see key action statement 8).…”
mentioning
confidence: 99%
“…Administering a single perioperative dose of dexamethasone decreases edema and ecchymosis formation over the first 2 postoperative days 97 ; there is also evidence that corticosteroids decrease pain and discomfort. 15,98,99 In addition, corticosteroids reduce nausea and vomiting in the immediate postoperative period, which may improve patient satisfaction. Conversely, there is some evidence that perioperative steroids may prolong postoperative ecchymosis 100 (see key action statement 8).…”
mentioning
confidence: 99%
“…Oedema and ecchymosis were reported to reach a peak level However, oedema is the usual result of soft tissue trauma and leads to excess interstitial fluid due to impaired lymphatic and venous systems. 19 Limited subperiosteal dissection is recommended to reduce oedema and swelling. 15 With a piezoelectric device, the relatively bulky ultrasonic tip generates heat and requires constant cooling by saline irrigation.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…However, oedema is the usual result of soft tissue trauma and leads to excess interstitial fluid due to impaired lymphatic and venous systems . Limited subperiosteal dissection is recommended to reduce oedema and swelling .…”
Section: Discussionmentioning
confidence: 99%
“…56 On a similar note, the routine use of corticosteroids, while being effective for the prophylaxis of postoperative nausea and vomiting, was considered not warranted, as it reduced edema and ecchymosis on the first 2 postoperative days only. 57 A Cochrane Database Systematic review found the evidence for this effect to be of low quality and concluded that in 2014, the available evidence did not support the use of corticosteroids for prevention of complications following facial plastic surgery. 58 Insufficient evidence supporting the use of corticosteroids in facial plastic surgery raises the question whether perioperative corticosteroid administration is safe.…”
Section: Corticosteroidsmentioning
confidence: 99%